2010
DOI: 10.1007/s00484-010-0363-8
|View full text |Cite
|
Sign up to set email alerts
|

Pollen counts and their relationship to meteorological factors in Ankara, Turkey during 2005–2008

Abstract: Pollen plays an important role in the development and exacerbation of allergic diseases. We aimed to investigate the days with highest counts of the most allergenic pollens and to identify the meteorological factors affecting pollen counts in the atmosphere of Ankara, Turkey. Airborne pollen measurements were carried out from 2005 to 2008 with a Burkard volumetric 7-day spore trap. Microscope counts were converted into atmospheric concentrations and expressed as pollen grains/m(3). Meteorological parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 25 publications
(26 reference statements)
1
8
0
1
Order By: Relevance
“…This finding might be due to the long distance transport of the olive tree pollens, which leads to sensitization far from the source of pollen [18]. It was shown that the pollen counts for Oleaceae reached to high values (90-1500) in the atmosphere of Ankara in the year 2007 [19]. Another explanation for this finding might be the increasing mobility within different regions of our country because of migrations, work, education or vacations.…”
Section: Discussionmentioning
confidence: 73%
“…This finding might be due to the long distance transport of the olive tree pollens, which leads to sensitization far from the source of pollen [18]. It was shown that the pollen counts for Oleaceae reached to high values (90-1500) in the atmosphere of Ankara in the year 2007 [19]. Another explanation for this finding might be the increasing mobility within different regions of our country because of migrations, work, education or vacations.…”
Section: Discussionmentioning
confidence: 73%
“…Again, Poaceae is the pollen type more studied. The authors Kizilpinar et al (2011) and Khwarahm et al (2014) show a strong positive correlation of grass pollen with INS.…”
Section: Correlations Between Mpin and Monthly Values Of The Meteorolmentioning
confidence: 92%
“…Previous studies found a relationship between the temperature in the preceding year and the annual pollen sum (Latałowa et al 2002; Rasmussen 2002). The influence of air temperature on pollen concentration has often been reported (Rodríguez-Rajo et al 2004; Puc2007, 2012; Kizilpinar et al2011). The impact of other meteorological parameters, such as precipitation, wind speed, and humidity, has also been reported (Latałowa et al 2002; Puc2007, 2012).…”
Section: Introductionmentioning
confidence: 95%